The effect of solid waste minimization towards the environment: A Case Study in Kedah - Su Abdullah, Muhammad Azharruddin; Omar, Salmah (Universiti Utara Malaysia, 2020)
Malaysia is one of the most successful developing countries in term of economic growth and stable politic conditions. Rapid economic transition and increasing of urban population will reflect the escalation of solid waste generation. In fact, it has become a threatened to human habitat nowadays as well as one of the critical challenges in sustainable development. Tonnes of solid waste are generated daily in Kedah which need appropriate management. Problems in the management of solid waste are tremendously affecting the daily lives of people and give negative impact to the environment. This paper present the result based on the study carried out on solid waste management practice by Solid Waste And Public Cleansing Management Corporation (SWCorp), Alor Setar, Kedah. This study was also designed to study the effect of solid waste minimization towards the environment in Kedah.